Shaking table tests on soil retaining walls reinforced by polymeric strips - Komak Panah, A.; Yazdi, M.; Ghalandarzadeh, A. (Geotextiles and geomembranes, 2015)
The seismic behavior of reinforced soil retaining walls with polymeric strips is examined. A series of 1-g shaking table tests were employed on 80 cm high reinforced-soil wall models. Also, some uniaxial tensile and pullout tests were performed in reduced-scale models to determine the best material to be used instead of polymeric strips in models. The effect of the length of reinforcement, number of steps and shape of the reinforcement arrangement (zigzag vs. parallel) on the failure mode, the wall displacement, and the acceleration amplification factor are investigated. Findings suggest that walls built with extensible reinforcement were flexible and the internal failure mechanism in the reinforced zone for these walls involved a bulging mode. The parallel implementation of reinforcements is more favorable as it decreases the displacements more than 50% before failure compared to the zig-zag arrangement. Also, wall displacement was reduced with a decrease and increase in the reinforcement length at bottom and top layers, respectively and this improved the wall behavior. Therefore, reducing the reinforcement length at the bottom of the wall without increasing the length of upper layers is not recommended as it can noticeably increase wall displacement from 1.2 to 7 times under different waves.